Bayer Filter Snapshot Hyperspectral Fundus Camera for Human Retinal Imaging. (3rd April 2017) - Kaluzny, Joel; Li, Hao; Liu, Wenzhong; Nesper, Peter; Park, Justin; Zhang, Hao F.; Fawzi, Amani A.
ABSTRACT: Purpose : To demonstrate the versatility and performance of a compact Bayer filter snapshot hyperspectral fundus camera for in-vivo clinical applications including retinal oximetry and macular pigment optical density measurements. Methods : 12 healthy volunteers were recruited under an Institutional Review Board (IRB) approved protocol. Fundus images were taken with a custom hyperspectral camera with a spectral range of 460–630 nm. We determined retinal vascular oxygen saturation (sO2 ) for the healthy population using the captured spectra by least squares curve fitting. Additionally, macular pigment optical density was localized and visualized using multispectral reflectometry from selected wavelengths. Results : We successfully determined the mean sO2 of arteries and veins of each subject (ages 21–80) with excellent intrasubject repeatability (1.4% standard deviation). The mean arterial sO2 for all subjects was 90.9% ± 2.5%, whereas the mean venous sO2 for all subjects was 64.5% ± 3.5%. The mean artery–vein (A–V) difference in sO2 varied between 20.5% and 31.9%. In addition, we were able to reveal and quantify macular pigment optical density. Conclusions : We demonstrated a single imaging tool capable of oxygen saturation and macular pigment density measurements in vivo . The unique combination of broad spectral range, high spectral–spatial resolution, rapid and robust imaging capability, and compact design make this system a valuable tool for multifunction spectral imaging that can be easily performed in a clinic setting.